Critical reflections on the Municipal Epidemiological Resilience Index used for public policy decision-making regarding the control of the COVID-19 pandemic in Colombia - Javier Eslava-Schmalbach; Alexandra Restrepo-Henao; Carol Guarnizo-Herreño; Juan Sebastián Castillo; Roman Vega-Romero; María Patricia Arbeláez; Rodrigo Pardo-Turriago; Paula Andrea Diaz; Hernando Gaitán-Duarte; Francy Cantor-Cruz; Lyda Osorio; Tatiana Andia; et al. (Revista de la Facultad de Medicina)
On June 2, 2021, the Colombian Ministry of Health and Social Protection, through Resolution No. 777, laid down the requirements to resume all restricted economic and social activities. Similarly, said Resolution established the Municipal Epidemiological Resilience Index (IREM by its acronym in Spanish) as a tool to support decision-making regarding this economic reactivation amid the third epidemic peak of COVID-19 in the country. The purpose of this article is to perform a critical analysis of the technical aspects of the IREM and to explore the feasibility of its implementation as a support for the resumption of economic and social activities as proposed in the Resolution. The present critical analysis emphasizes on the lack of a clear definition of epidemiological resilience that is consistent with the scientific literature. Furthermore, the face and content validity of the index, as well as the construct validity of the index and of its dimensions, are called into question and, therefore, the feasibility of using it to determine said resumption.